Study of Settlement Pattern in Klaten District, Central Java Province - Agus Dwi Martono (Forum Geografi, 1996)
This study is aimed at studying spatial distribution patterns of settlement, inluding their variations and respective influencing facctors. The ultimated objetives to be ahieved are studying variation of dsitribution patterns of settlement, and the contribution of socio-economi facctors to the existing distribution patterns of settlement under varying topographic areas. The study is conducted in Klaten District, covering 401 villages in the district. A survey method is secondary data analysis. Data are analyzed statistically using T test, varians analysis, correlation, and multiple regresion. The research shows that there is no significant differences in distribution patterns of settlement between the Merapi volcanic slope, the lowland, and the hilly zone. Physical factors are not significantly influencing the distribution patterns of settlement in various topographic zone. A neglegible ifference in the index distribution pattern of settlement can be observed. Hilly zone of the district reveals an index of 0.959. lower than those in the volcanis slope (1.035) and in low land (1.058). distribution patterns of settlement in various topographi zone are ditermine by different sets of socio-economic variables. In the volcanic zone two variables i.e. population density and the portion of sawah area are strongly influencing the distribution patterns of settlement. In this zone population density contributes more than the sawh area. Where as in the low land areas housing density dictates the distribution patterns of settlement. Other variables such as population density, road density, and utilities are less significantly influencing settlement patterns in the low land areas. The same relation between settlement pattern and housing density is also obvious in the distribution patterns of settlement in this hill. In general distribution patterns of settlement in the district are ontrolled by housing density, population density and road density. The higher housing densities, the distribution of hamlets are more spread. The same relation applies to population density. The higher road density the more clustered is the distribution patterns of settleent can be observed in the fast growing areas, rather than the opposite. No differences in distribution patterns of settlement can be observed among development unit areas (SWP) in the district.